Analisis Faktor Sustainabilitas Festival Budaya di Kota Jember Studi Tentang Jember Fesyen Carnaval - Ali, Moh; Suharto, Bambang; Maulidy, Ahmad Masrur; Lestari, Qatrunnada; Laksmi, Luh Putu Gita (Institut Seni Indoensia Surakarta, 2023)
The emergence of a large event known as the Jember Fashion Carnival has become an interesting phenomenon. The city of Jember, which initially had no history of carnivals and fashion, has now become the center of influential fashion carnivals in Indonesia and even on the world stage. This research uses a literature review approach to analyze the factors that have supported the sustainability of the Jember Fashion Carnival to date. The data source used in this research is secondary data, obtained through Google Scholar and Scopus to search for relevant journals. Journals that were found were then selected based on titles that matched the research focus. From the search results, the author succeeded in identifying 15 journals which were then summarized into 5 journals that represent a uniform view from all journals that have the same point of view. The results of this research show that in the context of cultural resource management, economic impact, community empowerment, and tourism promotion, the Jember Fashion Carnival (JFC) phenomenon and the fashion carnival phenomenon in Indonesia as a whole produce significant findings. Efficient management of local cultural resources has enabled JFC to become a driving force in local economic growth, with visible impacts in the tourism sector and related industries. The event also empowers communities by creating opportunities in the performing arts and creative industries. Apart from that, the carnival fashion phenomenon in Indonesia acts as a tourism promotion tool, introducing the richness of Indonesian culture to the world. The overall results of this research underscore the importance of wise management of cultural resources, community empowerment, and promotion of tourism through cultural events in achieving positive and sustainable economic impact